مقارنة النتائج العلاجية لخزع تضيق الإحليل بالليزر مع الخزع البارد - ناصر حسان; عبود أحمد (Latakia University Journal -Medical Sciences Series, 2013)
شملت الدراسة 40 مريضاً لديهم تضيق إحليل مفرد بطول أقل من 1سم ,تراوحت أعمارهم بين (20-75)سنة، راجعوا مشفى الأسد الجامعي(العيادة البولية والإسعاف) في اللاذقية بين عامي 2011-2012 . تم توزيعهم في مجموعتين (A)-(B). الأولى تم علاج المرضى باستخدام تقنية الهليوم ليزر. الثانية باستخدام الخزع بالسكين البارد (الخزع التقليدي). وتم توزيع المرضى في المجموعتين دون أي اعتبارات أو اختلافات إحصائية في الآلية الإمراضية لتضيق الإحليل ولا موقع التضيق , ولا الأمراض السريرية الناتجة عنها, سوى أن جميع المرضى لديهم تضيق مفرد واحد لا يتجاوز طوله 1 سم . تم تقييم فعالية العلاج باستخدام Uroflowmetry , حيث أجري لجميع المرضى قياس لمعدل جريان البول قبل العلاج وبعد العلاج بـ 3 أشهر ثم بعد 6 أشهر.[1] وأظهرت الدراسة الإحصائية فروقاً واضحة في كفاءة العلاج لصالح الخزع بالليزر (0,05>P). كما قمنا بمقارنة نتائجنا بدراسات عالمية وأشرنا إلى مواقع التوافق معها . Our study included 40 patients with a single length of less than 1 cm Urethral Stricture, between the ages of (20-75) years, reviewed the Assad University Hospital (Urinary clinic and Emergency Room) in Latakia between 2011-2012. Patients were distributed in two groups (A) - (B) The first group were treated using the technique of laser helium. The second group treated using a cold knife (a traditional biopsy). Patients were distributed in both groups without any considerations or statistical differences in the Pathogenicity mechanism, the stricture site, or any clinical diseases caused by them, but that all patients have a a single Urethral Stricture that does not exceed a length of 1 cm. The effectiveness of treatment were then evaluate using Uroflowmetry, where all patients was conducted to measure the rate of flow of urine before treatment and after treatment at 3 months and then after 6 months. Statistical study showed clear differences in the efficiency of treatment in favor of laser Urethrotomy(0,05> P). As we compare our results with three global studies and pointed to the compatibility with sites.